The first Triassic dipteran (Insecta) from South America, with review of Hennigmatidae - Lara, Maria Belén (2013)
The first Triassic dipteran from South America is described based on an isolated wing from the lower Upper Triassic deposits of Argentina (Mendoza Province, Potrerillos Formation, Quebrada del Durazno locality). Trihennigma zavattierii gen. et sp. nov. is a member of the Mesozoic family Hennigmatidae, previously recorded only from Eurasia. A key for the genera and species of Hennigmatidae is provided and systematic position of the taxa is discussed.